1976
DOI: 10.1111/j.1748-1716.1976.tb10238.x
|View full text |Cite
|
Sign up to set email alerts
|

β2‐Adrenoceptors Facilitating Noradrenaline Secretion from Human Vasoconstrictor Nerves

Abstract: Isolated biopsy specimens of human peripheral arteries and veins, preincubated with 3H-(-)- noradrenaline (NA) to label the neural stores of NA, were used to study the Beta-adrenoceptors previously found to increase the secretion of 3H-NA evoked by electrical field stimulation of the adrenergic nerves of this tissue. The increase in nerve stimulation induced secretion of 3H-NA caused by 0.04 muM isoprenaline was prevented by 1 muM propranolol. This beta-blocking drug by itself slightly but significantly depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1

Year Published

1980
1980
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(38 citation statements)
references
References 5 publications
4
33
1
Order By: Relevance
“…The relatively selective fi2-adrenoceptor agonists, terbutaline and salbutamol, enhance transmitter release in human omental arteries and veins, whereas the fll-adrenoceptor agonist, H 110/38, does not (Stjarne & Brundin, 1976).…”
Section: Statistical Analysis Of Resultsmentioning
confidence: 99%
“…The relatively selective fi2-adrenoceptor agonists, terbutaline and salbutamol, enhance transmitter release in human omental arteries and veins, whereas the fll-adrenoceptor agonist, H 110/38, does not (Stjarne & Brundin, 1976).…”
Section: Statistical Analysis Of Resultsmentioning
confidence: 99%
“…However, propranolol by itself did not decrease efflux, in contrast to the observation of these previous workers. Others have also described the inability of propranolol to reduce stimulation-induced efflux in various test preparations Starke et al, 1975;Stjarne & Brundin, 1976) and some have interpreted this as signifying a minor physiological role for presynaptic f-receptors under ordinary conditions of neuronal excitation.…”
Section: Discussionmentioning
confidence: 99%
“…The mean pD2 values in 13 tissues each for a-and P-mediated responses was 6.45 and 5.36, respectively. Although fl,-receptors have a greater affinity for noradrenaline than do #2-receptors, the presynaptic sites which interact with isoprenaline do not clearly fall into the former category (Dahloff, Ablad, Borg, Ek & Waldeck, 1975;Stjarne & Brundin, 1976). f2-Receptor agonists but not a fl-agonist enhanced transmitter efflux in human omental artery and vein preparations (Stjarne & Brundin, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…However in a study comparing the effects of atropine and salbutamol it was noted that with comparable increases in heart rate salbutamol increased cardiac output while atropine did not (Gibson & Coltart, 1970). Again, stimulation of presynaptic 132-adrenoceptors has been shown to release catecholamines from human vasoconstrictor nerves (Stjarne & Brundin, 1976) and this may have contributed to the rise in systolic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Salbutamol has been shown to increase supine heart rate in previous studies (Leitch et al, 1976;Philips et al, 1980;Kennedy & Simpson, 1969) and the specific 32-adrenoceptor antagonist, ICI 118,551 (Bilski et al, 1983) has been shown to abolish this increase in heart rate (McCaffrey et al, 1986) indicating that it is mediated by the 12-adrenoceptor. However the mechanism of the rise in heart rate is unclear and may be partly reflex, secondary to peripheral vasodilation or due to direct stimulation of P2-adrenoceptors in the heart (Stiles et al, 1983) or stimulation of presynaptic 132-adrenoceptors facilitating noradrenaline release at the sympathetic nerve endings (Stjarne & Brundin, 1976).…”
Section: Discussionmentioning
confidence: 99%